ANALISIS MANAJEMEN PROYEK PEMBANGUNAN RUMAH SUSUN LANJUTAN DI DESA KENTEN LAUT PROVINSI SUMATERA SELATAN - Nike Zuraidah; Herri Purwanto; Ami Warti (Fakultas Teknik, Universitas Wiraraja, 2022)
In the implementation of the construction of a construction project, there are three main things, namely cost, quality and time, which are interrelated, where a project can be completed on time with minimal costs and of good quality. In today's technological developments, especially in construction engineering management, to assist the work, many applications have been made in the completion of construction project engineering management. One of them is the Microsoft Project 2010 application, which can simplify the planning and implementation of a project schedule. The construction of advanced flats in Kenten Laut Village, South Sumatra Province, in the 18th week has experienced a time delay of 26% which should have reached 36% progress schedule, but the realization is only 10%. This is due to obstacles during the construction of the ground floor structure (foundation work). To speed up the work time, a re-planning of work productivity and work duration was carried out with the Microsoft Project 2010 application. From the re-planning of the advanced flat construction project in the village of Kenten Laut, South Sumatra province, structural work which includes columns, beams and floor slabs can be accelerated with a duration of work from 168 days to 132 days.